The Influence of CAR, FDR, Inflation, GDP, Mudharabah Financing, and Musyarakah Financing on NPF of Islamic Commercial Banks in Indonesia - Bambang Iswanto; Ibadurrahman Ibadurrahman (Global Review of Islamic Economics and Business, 2022)
Islamic finance in Indonesia has shown significant development. The development of Islamic finance will increase the growth of Islamic banks and further gives more positive impacts. However, with the development of Islamic banks, financing risks cannot be avoided because the strategic function of banks is to distribute funds to the public for the sustainability of the country's economy and the welfare of the community. This study aims to determine the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), inflation, Gross Domestic Product (GDP), Mudharabah financing, and Musyarakah financing on the financing risk of Islamic commercial banks in Indonesia for the period of 2015-2021. In contrast to the previous study, this research also sheds light on the zakat instrument as one of the GDP variables. This research is quantitative using multiple linear regressions. The sampling technique used is a purposive sampling technique with eight Islamic commercial banks, out of 14 as the population, taken as the sample. The results of this study indicate that CAR, FDR, and inflation have a significant negative effect on Non-Performing Financing (NPF). While, GDP and Mudharabah financing have a significant positive effect on NPF.